Indirect charitable assistance to Russia from American and Russian organisations and individuals - Vladislav Tarelko (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2024)
In the article has been attempted to consider the history of distant relief from the American and Russian organizations and individuals in favor of Russian disadvantaged children and orphans, sick and wounded Russian soldiers during the World War I. At the moment, in the Russian and American historiography, humanitarian cooperation between Russia and the United States is presented very fragmentally and haphazardly, and this topic has not received the deserved attention of researchers at all. Consequently, the author has identified the following purpose of this article – to summarize and expand the available material about the American and Russian relief and humanitarian assistance, to identify the features, forms and instruments of its activities, as well as to draw a general conclusion about the scale and benefits of the aforementioned assistance to Russia during the European war. The article was written on the basis of materials from the American and Russian periodicals, published documents and archive sources stored in the funds of The Russian State Historical Archive, the Archive of the Foreign Policy of the Russian Empire of the Ministry of Foreign Affairs of the Russian Federation, the Russian State Archive of the Navy. As a result, the author concluded that this assistance was of a national coverage and was expressed by both temporary and permanent American relief organizations. Russian organizations, which were under the auspices of Russian diplomatic authorities in the United States, set goal to collect funds through various entertainment events. Nevertheless, these donations took a small part in solving the problem of shortage of sanitary property. In general, both sides engaged in charitable activities not only out of a sense of compassion and a sincere desire to provide all possible assistance, but also within the framework of public diplomacy aimed at creating a favorable image of their country and stimulating friendly relations between Russia and the United States.